ANALISIS QUALITY CONTROL MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) PADA PRODUK GRILLE AIR INLET - Lia Milana; Whydiantoro Whydiantoro; Fikri Nur Hamzah (Universitas Widyatama, 2024)
PT Solo Plastik Indonesia is a company that produces plastic motor vehicle components. The standard set by the government regarding defective products is zero defect. From the data obtained in 2023 at PT Solo Plastik Indonesia, it shows that the percentage of defective products that occurred reached 33% so that the target was not met. To solve the problem, the Failure Mode and Effects Analysis (FMEA) method is used to identify potential failures in the product, consider the risk of failure, and identify the risk of failure, as well as identify and implement corrective actions to address the most important problems. Based on the results of the study, the highest defect was obtained, namely silver defect of 76%. The causes of defects are caused by human factors, machines, materials, and methods. Based on the research results, the highest RPN value on silver defects is 140 points with the cause of silver defects from material factors, namely contamination from other materials. Controlling the cause of the silver defect problem is by paying more attention to the cleanliness of the machine mold and paying more attention to the inspection of the material to be used. It is expected that by tightening the inspection of materials before use, it can have a significant impact on product quality as expected to avoid defects. Keywords: PT Solo Plastik Indonesia, Quality Control, Failure Mode and Effect Analysis (FMEA)